A Putative Efflux Transporter of the ABC Family, YbhFSR, in Escherichia coli Functions in Tetracycline Efflux and Na+(Li+)/H+ Transport - Feng, Zhenyue; Liu, Defu; Wang, Lizi; Wang, Yanhong; Zang, Zhongjing; Liu, Zhenhua; Song, Baifen; Gu, Liwei; Fan, Zhaowei; Yang, Siyu; Chen, Jing; Cui, Yudong (Frontiers in Microbiology, 2020)
ATP-binding cassette transporters are ubiquitous in almost all organisms. The Escherichia coli genome is predicted to encode 69 ABC transporters. Eleven of the ABC transporters are presumed to be exporters, of which seven are possible drug export transporters. There has been minimal research on the function of YbhFSR, which is one of the putative drug resistance exporters. In this study, the ybhF gene of this transporter, was characterized. Overexpression and knockout strains of ybhF were constructed. The ATPase activity of YbhF was studied using the malachite green assay, and the efflux abilities of knockout strains were demonstrated by using ethidium bromide (EB) as a substrate. The substrates of YbhFSR efflux, examined with the minimum inhibitory concentration (MIC), were determined to be tetracycline, oxytetracycline, chlortetracycline, doxycycline, EB and Hoechst33342. Furthermore, tetracycline and EB efflux and accumulation experiments confirmed that the substrates of YbhFSR were tetracyclines and EB. The MIC assay and the fluorescence tests results showed tetracyclines are likely to be the major antibiotic substrate of YbhFSR The existence of the signature NatA motif suggested that YbhFSR may also function as a Na+/H+ transporter. Overexpression of YbhF in E. coli KNabc lacking crucial Na+/H+ transporters conferred tolerance to NaCl, LiCl, and an alkaline pH. Together, the results showed that YbhFSR exhibited dual functions as a drug efflux pump and a Na+ (Li+)/H+ antiporter.